ADVANCE CARE PLANNING TOOLS AND RESOURCES FOR THE PEOPLE CARING FOR PERSONS WITH SERIOUS ILLNESS. (11th November 2018) - Dobbs, D J; Waters, L
Abstract: With the passage by the Centers for Medicare and Medicaid (CMS) in 2016 to reimburse physicians and other qualified health professionals for advance care planning (ACP) services across multiple health care settings, there has been an increase in the demand for education, training and tools for providers and caregivers about advance care planning communication for persons with serious illness. Approaches may vary depending on the population and setting of care. The papers in this symposium present ACP educational resources and tools for different health care providers and caregivers in a variety of health care settings. The first paper presents findings from a mixed-methods study that examines caregivers' perspectives about a dementia-specific end-of-life planning tool that incorporates both values and preferences. The second paper presents findings from a palliative care education in assisted living program for licensed nurses that focuses on ACP discussions with residents and their families that was piloted in Florida. The third paper focuses on increasing ACP in primary care through the Medicare Wellness Visit that has a physician champion and a dedicated nurse care manager, as part of a HRSA Geriatric Workforce Enhancement Program at two academic primary care practices. The fourth paper surveyed emergency medical technicians and paramedics about how prepared they are for emergency calls specific to Do Not Resuscitate orders and Medical Orders for Life Sustaining Treatment (MOLST). The discussant will address the value and benefits of each of the ACP educational resources presented in the symposium.